Comparing the bio-fertilizer quality of co-composted municipal organic wastes of different mix ratio: evidence from Tigray, northern Ethiopia - Kassa Teka; Tigist. A. Gessesse; Yemane Welday (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: There is an increasing trend of using sewage sludge co-composting to produce bio-fertilizers for use in agriculture. However, existing studies on the quality of the produced compost came out with contradicting results, which hinder its sustainable utilization. Hence, this study aimed at assessing the quality of sludge based compost for agricultural use.